OPTIMASI PARAMETER PROSES 3D PRINTING TERHADAP KEKUATAN TARIK FILAMENT ABS MENGGUNAKAN METODE TAGUCHI - Reza Dwi Putra Putra; Zaldy Sirwansyah Suzen; Hasdiansah (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
3D printing technology is a technique that uses a material filling method to print products, which is usually called the Additive manufacturing technique. This technique has often been used in various industrial fields, including construction, health, and prototyping. Making 3D printing is what is sought to replace metal materials. Of the many 3D printing technologies, the most frequently used is Fused Deposition Modeling (FDM). The workings of the FDM machine is by means of thermoplastic extrusion through a hot nozzle at a melting temperature, then the manufacture is made layer by layer to form a product. The purpose of this research is to optimize the parameters of the 3D printing process using ABS filament for tensile strength using the Taguchi L9 OA method. The various process parameters that will be used in this research are Nozzle temperature °C, Bed temperature °C, Layer Height mm. that the optimal process parameter values ​​for the tensile strength of ABS filament are Nozzle Temperature 245°C, Layer Height 0.20 mm, Bed Temperature 90°C.